Pengaruh Kebijakan Dividen terhadap Trading Volume Activity pada Sektor Perbankan di Bursa Efek Indonesia - Syafikah, Nurul; Musa, Muhammad Ichwan; Aslam, Annisa Paramaswary; Ramli, Anwar; Anwar, Anwar (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the effect of dividend policy on Trading Volume Activity (TVA) in the banking sector listed on the Indonesia Stock Exchange. The background of this research lies in the fact that the banking sector has the highest transaction value and that dividend policy is considered a signal of a company's prospects, which can influence stock trading activity. This research employs a quantitative approach using secondary data analysis obtained from financial statements and stock trading data of ten banks during the 2022–2024 period. Dividend policy is proxied by the Dividend Payout Ratio (DPR) as the independent variable, while Trading Volume Activity (TVA) serves as the dependent variable. The analytical technique used is panel data regression. The results show that DPR has a positive and significant effect on Trading Volume Activity (TVA). The higher the dividend paid, the greater the trading activity of the bank’s stock. These findings suggest that dividend announcements play an important role in investor decision-making and market responses within the banking sector.